Perancangan Lambung Trimaran pada Floating House sebagai Solusi Hunian dan Mobilitas di Kawasan Karimunjawa - Hamdi Fahrezi; Good Rindo; Deddy Chrismianto; Sapto Wiratno Satoto (Politeknik Negeri Batam, 2026)
Karimunjawa is a marine tourism destination that recorded 42,681 tourist visits in 2024. The increasing number of visitors has not been matched by adequate accommodation facilities, creating a need for alternative housing that supports sustainable tourism. This study aims to design and analyze a trimaran hull for a floating house suitable for the environmental conditions of Karimunjawa waters. The trimaran configuration was selected because it provides stability, a larger deck area, and lower resistance than a monohull. A systematic variation method with equal displacement was applied to three hull configurations: symmetric, asymmetric flat outside, and asymmetric flat inside. Modeling and analyses were conducted using AutoCAD, Maxsurf, and Rhinoceros based on local wave, current, and tidal data. The performance of each model was evaluated through resistance, stability, and seakeeping analyses. The results indicate that the symmetric hull provides the best performance, with a total resistance of 15,332 N at a design speed of 10 knots and a displacement of 38.59 tons. The design satisfies the stability criteria of IMO A.749(18) Chapter 3, MSC 36(63) HSC Code Annex 7, and the seakeeping criteria of NORDFORSK 1987. Economic analysis indicates that the symmetric configuration offers the highest cost efficiency.